2022
DOI: 10.1002/cl2.1207
|View full text |Cite
|
Sign up to set email alerts
|

Policies and interventions to remove gender‐related barriers to girls' school participation and learning in low‐ and middle‐income countries: A systematic review of the evidence

Abstract: Background Gender disparities in education continue to undermine girls' opportunities, despite enormous strides in recent years to improve primary enrolment and attainment for girls in low‐ and middle‐income countries (LMICs). At the regional, country and subnational levels gender gaps remain, with girls in many settings less likely to complete primary school, less likely to complete secondary, and often less likely to be literate than boys. The academic and policy literatures on the topic of gender‐related ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 273 publications
(880 reference statements)
0
27
0
Order By: Relevance
“…Rheinländer et al, for instance, highlighted the role of sanitation for girls’ secondary schooling rates [ 64 ]. A recent review identified several promising interventions to remove barriers to girls’ school participation and learning in low- and middle-income countries, including lack of water and sanitation [ 22 ]. In terms of nutritional environment, school-based food assistance could provide students to have at least one proper meal a day, further improving both health and education outcomes jointly [ 23 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rheinländer et al, for instance, highlighted the role of sanitation for girls’ secondary schooling rates [ 64 ]. A recent review identified several promising interventions to remove barriers to girls’ school participation and learning in low- and middle-income countries, including lack of water and sanitation [ 22 ]. In terms of nutritional environment, school-based food assistance could provide students to have at least one proper meal a day, further improving both health and education outcomes jointly [ 23 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have several implications for future research. First, there is a need for well-designed studies on tackling barriers to schooling in settings where secondary schooling is persistently low [ 22 , 73 ]. Our work can inform future schooling interventions which aim to assess strategies to reduce the number of adolescents who leave school early.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are mixed results on educational impact of programmes that promote safe spaces/girls' clubs and life skill development through female mentors. Psaki, Haberland, Mench, Woyczynski, andChuang, 2022 andAshraf cited in Psaki et al, 2020 found a small but statistically significant effect sizes of safe spaces on enrolment, though they observe that there no effects on absenteeism or academic skills. While providing a space for girls to meet with female mentors may reduce the isolation disadvantaged adolescent girls face in many settings and build their social assets, there is limited evidence that mentored groups alone can improve educational outcomes, especially academic skills unless key components on literacy, numeracy and financial training are integrated in such programmes (ibid).…”
Section: International Evidencementioning
confidence: 98%
“…Research consistently shows a lack of awareness and implementation of gender mainstreaming practices (Gurung & Rajbanshi, 2020;Kitta & Cardona Moltó, 2022;Nurhaeni & Kurniawan, 2018). Given the increasing recognition in research that gender equity calls for a strong intervention (Psaki et al, 2022;Shih & Wang, 2021), this research aims to identify the mainstreaming of gender perspective practices and the challenges in modular instruction. Recognizing the challenges in promoting gender-fair practices was essential in proposing intervention measures for crafting the syllabi and modules.…”
Section: Introductionmentioning
confidence: 99%